The Effect Of Phoenix Dactylifera L. Pinnae Reinforcement On The Mechanical And Thermal Properties Of Polymer Composite (Journal of the College of Basic Education, 2019)
Phoenix dactylifera l. pinnae (the green leaves of dates palm) were used as natural reinforcing (strengthening) fibers to improve the mechanical properties of polyester as a matrix material, the fibers of the green leaves of dates palm were used in two lengths, 10 and 20mm with five rates of 0, 2.5, 5, 10, and 20% , where the reinforcing with the leaves fibers increases the hardness strength from 76.5 to be about 86.55, the Impact value raised from about 0.313 to 0.461, in addition to that the flexural strength from 2.66 to be about 55, and the thermal conductivity increases from 2.54 ????∕????.℃ to 5.41 ????∕????.℃.The results of the present search explains that the composite samples reinforced at rate 20% and 10mm fiber length gives the best results.